A case study on the e-book use among students of the UP School of Library and Information Studies - Larracas, Wyndel James S.; Surmieda, Janny S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
This study focused on identifying the electronic book usage among undergraduate and graduate students enrolled at the UP School of Library and Information Studies. The study determined the level of ebook awareness among UP SLIS students and identified the extent of ebook usage. It also explored factors that contribute to the use and non-use of electronic books and UP SLIS students' format preferences.
A survey was used to gather data from 112 BLIS and 84 MLIS students enrolled during the first semester of A.Y. 2014-2015. Findings revealed that 54.46% of BLIS and 71.43% of MLIS respondents are aware of electronic books and were able to give a clear definition of the digital format. Majority of the respondents have expressed using electronic books in the past and cited accessing electronic books thru the Web OPAC and other free Webpages. Most respondents also identified "home, dormitory or boarding house" as their location of ebook access. 60.67% of undergraduate ebook users used the format thru the use of their personal computers while 48.72% of graduate ebook users stated mobile devices as their medium of electronic book use. Most BLIS and MLIS respondents used electronic books on an occasional basis. They also stated using the electronic format for assignments and research. The results of the study also revealed that most e-book users find the format "available online" and "convenient", citing it as their top reasons for using e-books. However, majority of ebook users expressed their preference of the conventional printed book over the electronic format. On the other hand, BLIS and MLIS ebook non-users still preferred the print book over its electronic counterpart but would still consider using e-books in the future.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Electronic books -- Philippines -- Quezon City -- Use studies